Annual Pattern on Abundance and Sex Ratio Distribution of Selected Fish Fauna of Ikere Gorge Reservoir, Oyo State, Nigeria - Adeosun, Festus Idowu (Borneo Journal of Resource Science and Technology, 2019)
Sex ratio affects the growth of wild population, thus, with the declining wild fish population, the study was designed to determine the effect of seasons on the sex ratio of fish population from Ikere Gorge, Nigeria for 18 months. Fish composition, diversity, distribution and abundance were determined according to standard methods. Sexes were determined and sex ratio was calculated using a standard method. A total of 5,823 fish specimens were caught during the period. The captured fish species were identified and classified into 34 species belonging to 13 families. The species richness was higher in the dry months than in the wet months. Fish diversity indices and evenness revealed a better diverse and even ecosystem in the wet season than the dry season. A marked significant difference (p < 0.05) was observed between the species in the dry months than the wet season. Chrysichthyes nigrodigitatus (35.07±7.59a) was significantly (p < 0.05) more abundant than the other species in the dry season. The sex ratio was skewed in favour of the female populations for C. nigrodigitatus, Tilapia melanopleura and Sarotherodon galilaeus but the reverse was the case for L. niloticus population. No monthly variation was observed in sex ratio of the species. The fish fauna from Ikere Gorge showed marked variations in the catch composition between the dry and wet months. C. nigrodigitatus and the Cichlids (Hemichromis fasciatus, S. galilaeus, Tilapia macrocephla and T. melanopleura) were present all year.